Neutron-physical characteristics of a system of quasi-infinite depleted uranium blanket – particle accelerator. Monte Carlo simulation - Bukhal, O.V.; Husak, K.V.; Zhuk, I.V.; Voronko, V.А.; Sotnikov, V.V.; Zhadan, A.А.; Baldin, A.А.; Tyutyunnikov, S.I. (Вопросы атомной науки и техники, 2019)
Simulation of a quasi-infinite uranium target irradiated by 1 GeV proton and deuteron particles with the help of FLUKA simulation package was carried out. Neutron spectra and neutron flux in a target volume were obtained. ²³⁵U(n,f), ²³⁸U(n,f), ²³⁸U(n,g) reaction rates in a target were determined. Beam particle power multiplication were calculated. Проведено моделювання опромінення квазінескінченої уранової мішені потоком протонів і дейтронів з енергією 1 ГеВ з використанням комп'ютерного коду FLUKA. В результаті моделювання отримані нейтронні спектри і потоки нейтронів в обсязі збірки. Визначено швидкості реакцій ²³⁵U(n,f), ²³⁸U(n,f), ²³⁸U(n,g) у мішені. Розрахований коефіцієнт посилення потужності налітаючого пучка частинок. Проведено моделирование облучения квазибесконечной урановой мишени потоком протонов и дейтронов с энергией 1 ГэВ с использованием компьютерного кода FLUKA. В результате моделирования получены нейтронные спектры и потоки нейтронов в объеме сборки. Определены скорости реакций ²³⁵U(n,f), ²³⁸U(n,f), ²³⁸U(n,g) в мишени. Рассчитан коэффициент усиления мощности налетающего пучка частиц.